2012
DOI: 10.1103/physrevb.86.014409
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-controlled ferromagnetism in iron phthalocyanine films due to one-dimensional iron chains

Abstract: Using magneto-optical Kerr effect, SQUID magnetometry and magnetic circular dichroism spectroscopy, ferromagnetism was found below 4.5K in iron phthalocyanine thin films grown by molecular beam epitaxy. The stacking of the molecules can be controlled via deposition temperature and substrate choice. The molecules self-assemble such that quasi one-dimensional iron chains form. The chains are limited in length by the grain size or film thickness which is manipulated using judicious growth methods. Magnetic hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 36 publications
5
55
0
Order By: Relevance
“…These planes are normal to the substrate and correspond to the (001) and (100) spacings, respectively, when using the α‐phase structure derived by Hoshino et al for CuPc . We note that the existing indexed structures for FePc correspond to a high temperature preparation traditionally associated with the β‐phase, and that using the structure of α‐CuPc to interpret the diffraction features of FePc films deposited at room temperature is an approach that has been commonly used by other groups . The TEM pattern is as expected from previous studies of the effect of PTCDA on metal phthalocyanine films, although it has been observed that the templated phase can also display (001) planes in TEM due to the spread in the orientation of the molecular crystals …”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…These planes are normal to the substrate and correspond to the (001) and (100) spacings, respectively, when using the α‐phase structure derived by Hoshino et al for CuPc . We note that the existing indexed structures for FePc correspond to a high temperature preparation traditionally associated with the β‐phase, and that using the structure of α‐CuPc to interpret the diffraction features of FePc films deposited at room temperature is an approach that has been commonly used by other groups . The TEM pattern is as expected from previous studies of the effect of PTCDA on metal phthalocyanine films, although it has been observed that the templated phase can also display (001) planes in TEM due to the spread in the orientation of the molecular crystals …”
Section: Resultssupporting
confidence: 63%
“…Transition metal phthalocyanines (MPcs) are very interesting as a new type of organic magnetic semiconductor that can offer tunability of the magnetic properties . Pcs are mostly planar aromatic molecules, existing in a large number of crystal phases, which can host a spin‐bearing ion in the center.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two factors may contribute to this: / XLPA T is obtained from a film of about 80 molecules thick, while / STM T is measured directly on the 2nd layer. Moreover, the Au substrate on the STM sample is a Au(111) single crystal, while the "smoothed" gold substrate is used for the thick film and XLPA experiments, even though highly ordered, 13,15 it is not a single crystal, and the overall tilt may be larger.…”
mentioning
confidence: 99%
“…Using Oguchi's method, 25 the inter-chain interaction was estimated to be J < 10 −3 J , demonstrating quasi onedimensional character of FePc thin films.Similar to the powder specimen, thin film samples of FePc also show interesting magnetic properties. In particular, FePc thin films have non-equilibrium magnetic hysteresis loops below 5 K. [26][27][28] The coercivity in films of fixed thickness strongly depends on the deposition temperature, the measurement speed, and measurement temperature. 29 XMCD data of FePc/Au thin films reveals an xy anisotropy in the plane of the molecule.…”
mentioning
confidence: 99%